Helminthiasis-protozoal infestations of children under 1 year of age: age-related aspects. Analysis of the work of 2012-2021 - R. S. Arakelyan; V. A. Sinkov; E. A. Strelova; D. G. Abakumova; O. V. Airumyants (Лечащий Врач, 2025)
Objective. To study and analyze the epidemiological situation of the incidence of helminth-protozoal infestations in children under the age of 1 year of life for the period from 2012 to 2021.Materials and methods. During the analyzed period, 27674 cases of parasitic infestations in children under the age of 17 were registered in the Astrakhan region.Results. According to nosological forms, parasitic invasions were represented by two representatives of helminthiasis (ascariids and pinworms) and two representatives of protozoa (giardia and amoeba). Helminthiasis mainly prevailed – 72.7% (112 cases), including ascariasis – 1.8% (2 cases) and 98.2% (110 cases) – enterobiosis. Clinical manifestations of giardiasis in children were noted in the form of loose stools up to 3-4 times a day – 100% (39 people), vomiting after meals – 69.2% (27 people), fever up to 37.3 °C – 23.1% (9 people), pain in the epigastric region (when touching with a hand) – 89.7% (35 people), and allergic skin rashes – 15.4% (6 people). Amoebiasis in children under the age of 1 year proceeded in the form of complaints of loose stools (according to parents) – 100% (3 people), soreness during defecation and decreased appetite – 66.7% (2 people). Also, such children had stool with mucus – 33.3% (1 person). Ascariasis in children occurred in the form of complaints of stool disorder (alternation of constipation with diarrhea), nausea, pain in the umbilical region – 66.7% (2 people), as well as allergic skin manifestations in the form of urticaria – 33.3% (1 child). In addition, one child's parents noted a stool with mucus. Enterobiosis was clinically manifested in the form of complaints of itching and scratching in the perianal region – 100% (110 people), decreased appetite – 80.9% (89 people) and vomiting – 15.5% (17 people).Conclusion. The main causative agents of helminth-protozoal invasions in children under the age of 1 year were giardiasis, amoebiasis, ascariasis and enterobiosis. The so-called "leading" place among all parasitic infestations of children of this age group belongs to enterobiosis – 71.4%. Geographically, the incidence of parasitic infestations is higher in Astrakhan than in rural areas of the Astrakhan region.